(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
I propose that despite the nay-saying 1) positive psychology is justifiably a branch of humanistic psychology, and 2) a humanistic positive psychology would be salutary to the profession of psychology. From the standpoint of theory, I show how positive psychology shares humanistic psychology’s concern with what it means to be fully, experientially human, and how that understanding illuminates the vital or fulfilled life. However, I also show how the findings of positive psychology, particularly in the area "happiness" research - or what has recently been termed "human flourishing," stop short of the fuller aforementioned aims. Specifically, I show how positive psychology appears to oversimplify both the experience of human flourishing and its social-adaptive value. While the positive psychology findings on flourishing are useful in limited contexts, e.g., in terms of their implications for the attainment of pleasure, physical health, and cultural competency, they are inadequate with respect to the more complicated contexts of creativity, emotional depth, and social consciousness. I will detail the nature of these discrepancies, such as their implications for perception of reality, psychological growth, and capacity for self-reflection, and consider their role in an expanded vision of human resiliency.